Технології розпізнавання дезінформації в соціальних мережах - Шелестова, Анна (Видавництво Львівської політехніки, 2025)
This paper explores the evolution of technologies for detecting disinformation on social media platforms. As digital misinformation threatens public discourse and democratic processes, advanced technological solutions have become essential. The field has progressed from traditional media monitoring to sophisticated systems employing artificial intelligence, machine learning, neural networks, and automated fact-checking tools that can analyze vast datasets to identify misleading content in real-time. Despite these advancements, significant challenges persist regarding ethical implications, potential freedom of expression infringements, and algorithmic bias. The paper emphasizes that effective disinformation management requires collaboration between technology developers, policymakers, and academic institutions to create balanced approaches that combat misinformation while preserving civil liberties.
Keywords: дезінформація; соціальні медіа; штучний інтелект; перевірка фактів; регулювання